2018
DOI: 10.15694/mep.2018.0000013.1
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Gender Medicine in Medical Education at Austrian Universities – the Status Quo

Abstract: The work at hand examines the current status of the implementation of Gender Medicine in medical education at all Austrian universities. To date no systematic studies have been conducted on this subject. This study covers public as well as private universities.The methodology was to first conduct a document analysis, followed by a questionnaire survey.Analysis of the documents showed that Gender Medicine is often combined with affirmative action for women, equal treatment and/or gender studies. These subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In a study by Nachtschatt et al [30], it was suggested that, after being integrated into the biomedical curriculum, the real challenge was to ensure implementation in a sustainable way.…”
Section: How To Integrate Gender Medicine Into Medical Curricula: Bar...mentioning
confidence: 99%
“…In a study by Nachtschatt et al [30], it was suggested that, after being integrated into the biomedical curriculum, the real challenge was to ensure implementation in a sustainable way.…”
Section: How To Integrate Gender Medicine Into Medical Curricula: Bar...mentioning
confidence: 99%
“…Progress goes hand in hand with the creation of dedicated professorships, such as the professorship on gender‐sensitive prevention research at the Charité Berlin established in late 2019. In Austria, a group of researchers from the University of Vienna (Gender Mainstreaming and Diversity Office; Coordination Office for Equality, Affirmative Action for Women and Diversity) and the Medical University of Innsbruck are driving education in gender medicine by closely collaborating on the continuous development of sex‐ and gender‐sensitive medical curricula and producing publications on educational needs and methodology around the topic of gender medicine [14, 15]. At Bielefeld University, an entirely new study course on gender medicine is being established with a new professorship for gender‐specific medicine from April 2021.…”
Section: Resultsmentioning
confidence: 99%
“…In Germany, in other European countries and worldwide, efforts are being made to integrate sex, gender and further diversity categories into health professions education, with the focus so far on the integration into medical curricula (Verdonk et al, 2005;Ludwig et al 2015;Miller et al, 2016;Nachtschatt et al, 2018;Khamisy-Farah & Bragazzi, 2022). However, a survey of the German Medical Women's Association has shown that gender-sensitive aspects are not yet systematically integrated into the curricula of medical faculties in Germany (Ludwig et al, 2016;Dettmer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%